Knockdown of hexokinase 2 results in a decreased expression level of the glycolytic enzymes PFKP, BPGM, and GPI in RKO cell line - M. S. Fedorova; I. Y. Karpova; A. V. Lipatova; E. A. Pudova; Z. G. Guvatova; D. V. Kochetkov; A. V. Chaika; B. Y. Alekseev; M. V. Kiseleva; A. D. Kaprin; A. V. Kudryavtseva; A. V. Snezhkina (Вавиловский журнал генетики и селекции)
Colorectal cancer (CRC) is one of the most common malignant neoplasms in the world, and is characterized by a high mortality rate. The study of the key aspects of colorectal cancer formation and progression is necessary to develop new approaches to its therapy, as well as to search for new diagnostic, prognostic and predictive biomarkers of CRC. In many types of tumors, one of the key changes in metabolism is the  activation of glycolysis, which is associated with alterations in the expression of the main glycolytic enzymes and regulatory molecules. There is often an increase in hexokinase 2 (HK2) exogenous expression in tumor cells, which makes it a promising target for anticancer therapy. Quantitative expression analysis of 15 genes (GAPDH, ADPGK, ALDOA, ENO3, PFKL, PGK1, PGAM1, PKM2, ENO1, PDK1, PDK3, PFKP, ENO2, GPI, and BPGM), encoding the key glycolysis enzymes, as well as HIF1A gene was carried out in a modified RKO cell line, which constantly expresses the short hairpin RNA (shRNA) for the inhibition of hexokinase 2. A significant decrease in the expression of PFKP, BPGM, and GPI genes both at the mRNA (5, 86, and 93fold, respectively) and protein (2.5, 3.5, and 19fold, respectively) levels was revealed. Probably, the downregulation of GPI and PFKP is associated with a decrease in the amount of their substrates, glucose6phosphate and fructose6phosphate, under the inhibition of hexokinase 2. Nevertheless, the cause of a decreased mRNA level of these three enzymes, while the expression level of other glycolytic participants is constant, requires further investigation.